2021
DOI: 10.3390/phycology1020011
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterisation of Sargassum Inundation from the Turks and Caicos: Seasonal and Post Stranding Changes

Abstract: The Turks and Caicos Islands (TCI) have been affected by sargassum inundations, with impacts on the economy and environment. Sargassum removal can be costly, but sargassum use and valorisation may generate income and offset environmental damage. A significant barrier to the valorisation of sargassum is insufficient knowledge of its chemical makeup, as well as its seasonal variation and decay after stranding. The chemical characterisation of mixed sargassum and its constituent species and morphotypes (S. natans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…Chemical characterisation of many Sargassum species showed that metal content (in particular arsenic) severely hampers the prospects of using Sargassum species for food or feed. However, this seaweed's high metal sorption ability could offer a feasible and economical approach for removing industrial heavy-metal-bearing wastewaters that require efficient and cost-effective treatment [40]. Other non-conventional low-cost adsorbents were reviewed by Rafatullah et al [41].…”
Section: Discussionmentioning
confidence: 99%
“…Chemical characterisation of many Sargassum species showed that metal content (in particular arsenic) severely hampers the prospects of using Sargassum species for food or feed. However, this seaweed's high metal sorption ability could offer a feasible and economical approach for removing industrial heavy-metal-bearing wastewaters that require efficient and cost-effective treatment [40]. Other non-conventional low-cost adsorbents were reviewed by Rafatullah et al [41].…”
Section: Discussionmentioning
confidence: 99%
“…While many species of brown algae have been investigated for their composition and valorisation, most of what we know about these aspects of bloom forming pelagic sargassum, e.g. species, morphological types (morphotypes) and biomass composition, was published five to ten years after the initial arrival (in the tropical Atlantic) of pelagic sargassum [48][49][50][51][52][53][54]. Valorisation has been a relatively new dimension of sargassum science and policy.…”
Section: Technology and Valorisationmentioning
confidence: 99%
“…Some technologies are small-scale and can be rolled out cheaply to create benefits for affected communities or entrepreneurs, e.g. small biogas digesters for biomethane production, or sargassum storage for compost production (ideally mixed with other plant material or biological wastes) [54,[63][64][65][66][67][68]. Other use options require investment in sargassum specific technology, e.g.…”
Section: Technology and Valorisationmentioning
confidence: 99%
“…Sargassum influx events are now considered the new 'normal' for the region (Desrochers et al, 2020) and show a trend of increasing severity (The Sargassum Watch System (SaWS), 2022). As the region continues to adapt to this new reality, there has been a surge in research and publications on impacts (Milledge and Harvey, 2016;Ramlogan et al, 2017;van Tussenbroek et al, 2017;United Nations Environment Programme, 2018;Resiere et al, 2019), forecasting (Wang and Hu, 2017;Johnson et al, 2020;Marsh et al, 2021;Marsh et al, 2022), potential uses (Desrochers et al, 2020;Thompson et al, 2020;Amador-Castro et al, 2021;Oxenford et al, 2021;United Nations Environment Programme -Caribbean Environment Programme et al, 2021) and chemical composition (Devault et al, 2019;Davis et al, 2020;Nielsen et al, 2021;Devault et al, 2022;Tonon et al, 2022). Research into the sargassum phenomenon reveals considerable spatial and temporal complexities associated with management due to its transboundary nature and unpredictability (Cox et al, 2021).…”
Section: Introductionmentioning
confidence: 99%